Exploring the green features of converged networks. (8th June 2012) - Yang, Xiaodong
The converged network has been the trend of network development. It can not only provide advanced new features to the end users, but also provide a novel way of green computing to the network operators. This paper presented the idea of utilising converged networks for green network operations. The converged network-based solution is presented in detail and the benefits of the proposal are discussed. Mathematical analyses showed that the converged networks consume less network operation resources compared with non-converged networks and converged networks also perform better when the network operation scale is increased. Some open research issues and the future work are further discussed in the conclusion part of this paper.